THE SYSTEM OF INFORMATICS COMPETENCIES FOR THE MATHEMATICS TEACHER - Nadiia Ponomareva ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
As a result of the analysis of domestic and foreign standards of key competencies, basic and complete secondary education, teachers' training (in particular, mathematics teachers' training) and information technology specialists training, the system of informatics competencies of a mathematics teacher, developed by Yu. S. Ramskyi, was updated in terms of the structure, content and indicators of competencies formation. It has been found out that the formation of the informatics competencies of a mathematics teacher begins with basic informatics competencies, the further development of which occurs primarily in the competencies in system administration, web technologies, programming and systems analysis.